Taking decisions. (Journal of Parents and Teachers, 2014)
From a very early age, human beings are forced to face problems and decide solutions. Deciding is a complex activity that consists of evaluating, learning, teaching and, above all, implies misunderstanding.
Keywords: Decisions; conflict resolution; teaching to make decisions.